Linguistic and discursive features of mining news discourse in the Philippines - Diamante, Jennifier Tabernero; Cadiente, Glenda Doroja; Mabuan, Romualdo Atibagos (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Philippines is one of the mineral-rich countries in the world with an estimated US$840 billion worth of untapped mineral wealth, catapulting the mining industry as a significant economic player providing substantial contribution to the national revenue and generating employment opportunities for the Filipino people. However, the detrimental impact of mining to the country has also been heavily criticized as it causes massive potential destruction to environment and wildlife ecology such as acid mine drainage and contaminant leaching, soil erosion, and tailing impoundments among others. These conflicting interests are reflected in the mining discourses stoked or dimmed by media, which influence the readers’ construal of meanings in the mining texts, social actors’ roles in the mining industry, and the urderlying contexts of the mining reality. Drawing on critical discourse analysis, this study described the linguistic and discursive features of Philippine mining discourse in media texts. The study used 224 news articles published by three online portals within five years. Local news reports and peripheral discourses obtained through interviews with local “symbolic elites” in the identified mining communities and other archival documents supplemented the news texts. The UAM Corpus Tool, a software for linguistic tagging, complemented the manual analysis in identifying the social actor theme. Findings revealed that government actions, economic phenomenon, and political actors are the most prevalent themes in the mining news reports. Moreover, results showed that local news tends to focus more on the mining’s environmental impact, whereas the national news tends to put more premium on the mining’s economic impact. This means that the media allotted a much lesser spatio-temporal space for the environment and Indigenous Peoples’ cause. The findings further invalidate the assumptions that mining discourse is primarily concerned with environmental related issues.